PENGARUH STRATEGI BISNIS, KEMAMPUAN MANAJERIAL, DAN PENGETAHUAN AKUNTANSI PELAKU UMKM TERHADAP KINERJA UMKM BIDANG KULINER DI KABUPATEN PURBALINGGA - Muttaqin Abdillah; Dona Primasari (Universitas Ahmad Dahlan, 2019)
This study aims to determine and analyze the infl uence of business strategy variables, managerial abilities and accounting knowledge of SME actors on the performance of SMEs in the culinary fi eld in Purbalingga Regency. This study uses primary data, with the SME population in the culinary fi eld in Purbalingga district. The method used to determine the sample of the study was purposive sampling method, so that 61 respondents were obtained. The analytical method used is Multiple Regression Analysis. The results of this study indicate that business strategies, managerial capabilities and accounting knowledge partially and simultaneously infl uence the performance of SMEs. The implication of this research is that the performance of MSMEs can be improved by applying business strategies that are appropriate to the situation, MSME actors have adequate managerial skills and have good accounting knowledge.